Ancient apocalypse end of a civilization - Page, Cynthia; Peck Danielle; Cecil, Jessica; Bookbinder, Alan.; British Broadcasting Corporation; Learning Company (London, UK BBC Worldwide Limited, 2004)
"Traditionally, the disappearance of several ancient civilizations has been left to the theologians and historians to explain. Now the scientists have entered the fray. In this series geologists and climatologists explain their findings."
Disc 1 (50 min.). Episode 1. Death on the Nile ; Episode 2. Mystery of the Minoans -- Disc 2 (50 min.). Episode 3. The Maya Collapse ; Episode 4. Sodom and Gomorrah.
Title from container.
Library has: VDR-1574 (1 DVD), VDR-1575 (1 DVD).
Also available in Cantonese and Mandarin languages.
In English with Cantonese and Mandarin subtitles.
DVD videos, NTSC Region 3.
Keywords: Civilization, Ancient; Hazardous geographic environments